THU0188 Frequency of autoantibodies targeting pancreas in rheumatoid arthritis with and without secondary sjÖgren's syndrome. (1st June 2001) - Isik, A; Tunc, E; Kitapcýoglu, G; Kocanaogullarý, H; Inal, V; Doganavsargil, E; Gumusdis, G
Abstract : Background: Immune mediated diseases may be tissue specific such as insulin dependent diabetes mellitus (IDDM), or may be systemic such as rheumatoid arthritis (RA). Since impaired glucose tolerance have been reported in some connective tissue diseases. 1, 2 Objectives: we investigated the frequency of autoantibodies targeting pancreas in RA patients with and without Sjögren's syndrome (SjS). Methods: 103 RA patients, 26 with secondary SjS were included in this study. Serum islet cell antibodies (ICA), anti-insulin antibodies (AIA) and insulin receptor antibodies (IRA) were measured. Standard oral glucose tolerance test was performed if fasting or postprandial plasma glucose levels were elevated, or if any of the above mentioned antibodies were positive. Results: The frequencies of positive ICA, AIA and IRA in the whole group of patients with RA were 21.4%, 29.7% and 15.2%, respectively. There was no significant differences between the subgroups of RA patients with respect to OGTT results and autoantibodies (p > 0.05). However, we observed a significant difference between AIA positivity and disease duration (p < 0.05). Conclusion: Presence of autoantibodies targeting pancreas does not differ significantly in RA patients with and without SjS. These antibodies are not specific for IDDM, rather they are part of the autoimmune repertoire in systemic autoimmune diseases such as RA. References: Paolisso G, Valentini G, Giugliano D, et al . Evidence for peripheral impaired glucose handling in patients with connective tissue diseases. Metabolism 1991;40(9):902–7 Thomas DJ, Young A, Gorsuch AN, et al . Evidence for an association between rheumatoid arthritis and autoimmune endocrine diseases. Ann Rheum Dis. 1983;42(3):297–300